Nemarioc-AL and nemafric-BL phytonematicides : bioactivities in meloidogyne incognita, tomato crop, soil type and organic matter - Dube, Zakheleni Palane (My University, 2016)
Nemarioc-AL and Nemafric-BL phytonematicides, had been researched and developed from indigenous plants at the University of Limpopo, Green Technologies Research Centre, under the auspices of the Indigenous Cucurbitaceae Technologies (ICT) Research Programme. After the international 2005 cut-off withdrawal date of the highly effective methyl bromide nematicide from the agrochemical markets, management options on nematode population densities shifted to more environment-friendly alternatives. Nemarioc-AL and Nemafric-BL phytonematicides as environment-friendly alternatives to synthetic chemical nematicides had been consistent in nematode suppression under diverse conditions. In order to avoid challenges similar to those experienced with the use of synthetic chemical nematicides, the South African Fertiliser, Farm Feeds, Agricultural Remedies and Stock Remedies Act No. 36 of 1947 (amended) require that the product to be used in agriculture must first be registered with the National Department of Agriculture, Forestry and Fisheries, after extensive efficacy and bioactivity tests. The information on bioactivity of the phytonematicides is also critical in the effective application of the product for efficient management of nematodes. Information on bioactivities of Nemarioc-AL and Nemafric-BL phytonematicides on nematodes, plant and soil was not available. This study comprised eight objectives: (1) to examine whether (i) increasing concentration of cucurbitacin A and B would have impact on second-stage juvenile (J2) hatch of M. incognita, (ii) the Curve-fitting Allelochemical Response Dosage (CARD) model would quantify the three phases of density-dependent growth (DDG) patterns on J2 hatch when exposed to increasing cucurbitacin concentrations, (iii) computed J2 hatch inhibition concentration (EHIC) and xli CARD-generated D-values would be statistically similar, (iv) the CARD model would provide information on minimum inhibition concentration (MIC) and (v) J2 hatch inhibition would be reversible when cucurbitacins were diluted, (2) to determine whether (i) increasing concentration of Nemarioc-AL and Nemafric-BL phytonematicides would have impact on J2 hatch of M. incognita, (ii) the CARD model would quantify the three phases of DDG pattern on J2 hatch when compared to increasing phytonematicide concentrations, (iii) comparison of computed EHIC and CARD-generated D-values would be statistically comparable in magnitudes, (iv) the CARD model would provide information on MIC and (v) J2 hatch inhibition would be reversible when phytonematicides were diluted, (3) to establish whether (i) increasing concentration of cucurbitacin A and B would have impact on M. incognita J2 immobility, (ii) the CARD model would quantify the three phases of DDG pattern on J2 immobility when compared to increasing cucurbitacin concentration, (iii) comparison of computed J2 immobility concentration and CARD-generated D-values would be statistically comparable in magnitudes, (iv) the CARD model would provide information on MIC and (v) juvenile immobility would be reversible when cucurbitacins were diluted, (4) to test whether (i) increasing concentration of Nemarioc-AL and Nemafric-BL phytonematicides would have impact on M. incognita J2 immobility, (ii) the CARD model would quantify the three phases of DDG pattern on J2 immobility when compared to increasing phytonematicide concentrations, (iii) comparison of computed J2 immobility concentration and CARD generated D-values would be statistically comparable in magnitudes, (iv) the CARD model would provide information on MIC and (v) juvenile immobility would be reversible when phytonematicides were diluted, (5) to determine whether (i) increasing xlii concentration of cucurbitacin A and B would have impact on M. incognita J2 mortality, (ii) the CARD model would quantify the three phases of DDG patterns on J2 mortality when compared to increasing cucurbitacin concentration, (iii) comparison of computed lethal concentration (LC) and CARD-generated D-values would be statistically comparable in magnitudes and (iv) the CARD model would provide information on minimum lethal concentration (MLC), (6) to investigate whether (i) increasing concentration of Nemarioc-AL and Nemafric-BL phytonematicides would have impact on M. incognita J2 mortality, (ii) the CARD model would quantify the three phases of DDG pattern on J2 mortality when compared to increasing phytonematicide concentrations, (iii) comparison of computed LC and CARD-generated D-values would be statistically comparable in magnitudes and (iv) the CARD model would provide information on MLC, (7) to test whether (i) increasing concentrations of Nemarioc-AL and Nemafric-BL phytonematicides would impact on M. incognita J2 infectivity of susceptible tomato plant, (ii) the CARD model would quantify the three phases of DDG pattern (iii) generated inhibition concentration (IC) and CARD-generated D-values would be statistically comparable in magnitudes and (iv) the CARD model would provide information on MIC and (8) to determine whether nematodes can serve as bioindicators of Nemarioc-AL and Nemafric-BL phytonematicides in tomato plant roots/fruits, soil types and organic matter at different depths. To achieve these objectives, reliability of measured variables was ensured by using statistical levels of significance (P ≤ 0.05) and coefficient of determination (R2), with validity ensured by conducting three independent experiments over time. In Objective 1, pure cucurbitacin A and B concentration effects on J2 hatch were significant, with both exhibiting DDG patterns. xliii The DDG patterns demonstrated that J2 hatch was inhibited at low pure cucurbitacin concentrations and slightly stimulated at higher cucurbitacin concentrations. At 24-, 48- and 72-h exposure periods, cucurbitacin A reduced J2 hatch by 40‒67, 34‒66 and 34‒45%, respectively, whereas cucurbitacin B reduced J2 hatch by 12‒57, 3‒36 and 9‒54%, respectively. CARD model quantified the concentration ranges of the two pure cucurbitacins associated with the phases of DDG patterns. The J2 hatch was highly sensitive to cucurbitacin B and highly tolerant to cucurbitacin A, as shown by sensitivities values of 0‒2 and 5‒20 units, respectively. The CARD-generated MIC values for cucurbitacin A and B were 1.75‒2.88 and 1.31‒1.88 µg.mL-1, respectively. The conventionally generated J2 hatch inhibition concentrations were higher than CARD-generated D-values at all exposure periods for both pure cucurbitacins. The J2 hatch inhibition effect was not reversible for both pure cucurbitacins. In Objective 2, Nemarioc-AL and Nemafric-BL phytonematicide concentration effects on J2 hatch were highly significant (P ≤ 0.01), with both exhibiting DDG patterns. The DDG patterns demonstrated that J2 hatch inhibition increased with increase in phytonematicide concentrations. Relative to water control, Nemarioc-AL phytonematicide significantly reduced J2 hatch at 48-, 72-h and 7-d by 22‒92, 3‒79 and 1‒42%, respectively, whereas Nemafric-BL phytonematicide reduced it by 41‒93, 1‒80 and 12‒84%, respectively. The J2 hatch inhibition was highly sensitive to Nemarioc-AL and Nemafric BL phytonematicides, with sensitivity of 0‒1 and 0‒4 units, respectively. The conventionally generated J2 hatch inhibition concentrations at 50 and 100% were higher than CARD-generated D-values for both phytonematicides. The J2 hatch inhibition effect was not reversible for both phytonematicides. In Objective 3, pure cucurbitacin A xliv and B concentration effects on J2 immobility were significant, with both exhibiting DDG patterns. The J2 immobility over increasing concentrations of pure cucurbitacins had DDG patterns which were similar for conventional method and those from CARD model. The DDG patterns were characterised by stimulation of J2 immobility at low concentrations, followed by saturation at higher concentrations. The CARD model could not generate the D-values for comparison with JMC-values, but generated MIC-values for cucurbitacin A and B which were 0.5‒0.6 and 0.5‒0.7 µg.mL-1, respectively. The J2 immobility was moderately sensitive to both cucurbitacins with sensitivity of 4 units and the inhibition effect of the two pure cucubitacins was not reversible. In Objective 4, Nemarioc-AL and Nemafric-BL phytonematicide concentration effects on J2 immobility were highly significant (P ≤ 0.01), with both phytonematicides exhibiting DDG patterns. The DDG pattern had stimulation, saturation and inhibition effects for Nemarioc-AL phytonematicide, whereas for Nemafric-BL phytonematicide they had stimulation and saturation effects on J2 immobility as concentrations increased. The MIC-values for Nemarioc-AL and Nemafric-BL phytonematicides were 3.6‒115.2 and 0.1‒6.5%, respectively. The CARD generated D-values were comparable with computed JMC values for Nemafric-BL phytonematicide unlike for Nemarioc-AL phytonematicide. The J2 immobility was highly sensitive to the two phytonematicides with sensitivity values of 0‒4 and 0‒2 units, respectively. The effects on J2 immobility of the two phytonematicides were not reversible. In Objective 5, pure cucurbitacin A and B concentration effects on J2 mortality were highly significant (P ≤ 0.01), with both cucurbitacins exhibiting DDG patterns. The DDG pattern had stimulation, saturation and slight inhibition effects for both cucurbitacin A and B as concentrations increased. The xlv MIC-values for cucurbitacin A and B were 0.63 and 0.61 µg.mL-1, respectively. The CARD-generated D-values were higher than the computed LC-values for both cucurbitacin A and B, with J2 mortality being highly sensitive to cucurbitacin A and B, with sensitivity of 4 units for both cucurbitacins. In Objective 6, Nemarioc-AL and Nemafric-BL phytonematicide effects on J2 mortality were highly significant (P ≤ 0.01), with both phytonematicides exhibiting DDG patterns. The DDG pattern had stimulation effect at low phytonematicide concentrations and saturation effects at higher concentrations for both relative impact and CARD-generated graphs of J2 exposed to both phytonematicides. The MIC-values for Nemarioc-AL and Nemafric-BL phytonematicides were 1.12 and 0.67%, respectively. The CARD-generated D-values were higher than the computed LC-values for both phytonematicides and J2 mortalities were highly sensitive to Nemarioc-AL and Nemafric-BL phytonematicides with sensitivity value of 2 and 1 units, respectively. In Objective 7, Nemarioc-AL and Nemafric-BL phytonematicide concentrations had a highly significant effect on infectivity of M. incognita post-exposure on susceptible tomato seedlings. The relationship between infectivity and increasing concentrations of the two phytonematicides exhibited DDG patterns. The DDG patterns were characterised by stimulation effect at low Nemarioc AL phytonematicide concentrations and saturation effects at higher phytonematicide concentrations, whereas for Nemafric-BL phytonematicide slight inhibition, saturation and stimulation effects were observed. The CARD-generated inhibition concentrations for Nemarioc-AL phytonematicide were comparable with computed inhibition concentrations, whereas for Nemafric-BL phytonematicides, the values were not comparable. The MIC-values for Nemarioc-AL and Nemafric-BL phytonematicides were xlvi 0.2 and 0.7%, respectively and J2 infectivity were highly sensitive to the two phytonematicides, with sensitivity value of 2 and 0 units, respectively. In Objective 8, M. incognita was an excellent bioindicator in response to the application of two phytonematicides. The two phytonematicides significantly affected distribution of population densities of M. incognita across the tested soil types, with Nemafric-BL phytonematicide reducing population densities of M. incognita relative to Nemarioc-AL phytonematicide. The active ingredient of Nemafric-BL phytonematicide, cucurbitacin B tended to remain in the top layers of soil, where more roots accumulated, thereby reducing a relatively higher population densities of M. incognita than did active ingredient of Nemarioc-AL phytonematicide, cucurbitacin A which moved with water beyond the effective root zone. Soil type alone and phytonematicide alone had no effect on nematode numbers, whereas the interaction of soil type, phytonematicides and depth, the nematode population densities were inversely proportional to soil depth. The interaction of clay with any of the two phytonematicides, reduced M. incognita population densities compared to sand and loam interactions. More than 62% tomato root systems occurred in the top 0–25 cm depth. The interactions between organic matter levels, phytonematicides and depth had no effect on the population densities of M. incognita. The two phytonematicides were able to reduce nematode population densities throughout the soil column in all four soil types and organic matter levels. Cucurbitacin residues were not detected in all tomato fruit samples. In conclusion, Nemarioc-AL and Nemafric-BL phytonematicides have bioactivities on J2 hatch, J2 immobility, J2 mortality and J2 infectivity. The CARD model quantified the three phases of DDG patterns for most of the variables. Even though CARD-generated inhibition xlvii concentrations at 50 and 100% were not comparable with computed values for pure cucurbitacins they were for most phytonematicide variables, the model was able to generate excellent MIC-values for all variables. The inhibition effects of the two phytonematicides were irreversible. The major findings of this study were that the two phytonematicides exhibited DDG patterns for all variables tested and that the CARD model could be adopted for the in vitro evaluation of phytonematicides. Meloidogyne incognita was an excellent bioindicator on movement of two phytonematicides across soil types and organic matter levels at different depths. Nemarioc-AL and Nemafric-BL phytonematicides did not leave any cucurbitacin residues in tomato fruit. The information on bioactivities of the two phytonematicides generated in this study provides a much needed data for the registration of the products as required by the law. Proposed future research area includes, microscopy study of molecular effects of the phytonematicides on nematodes post-exposure.
Thesis (Ph. D. Agriculture (Plant Production)) -- University of Limpopo, 2016.
Keywords: Indigenous Cucurbitaceae; Phytonematicides; Nemarioc-AL; Nemafric-BL; Meloidogyne incognita; Cucurbitales; Plant nematodes; Plant nematodes -- Biological control; Nematocides